Heat and mass transfer effects on MHD flow past an inclined porous plate in the presence of chemical reaction - Sandhya, Akuri; Reddy, G. V. Ramana; Deekshitulu, G. V. S. R. (Zielona Góra: Uniwersytet Zielonogórski)
The impact of heat and mass transfer effects on an MHD flow past an inclined porous plate in the presence of a chemical reaction is investigated in this study. An effort has been made to explain the Soret effect and the influence of an angle of inclination on the flow field, in the presence of the heat source, chemical reaction and thermal radiation.
Keywords: chemical reaction; heat source; inclined plate; porous medium; thermal radiation